Basal ganglia: physiological, behavioral, and computational studies - Ahmed A. Moustafa (Frontiers Research Topics, 2015)
The basal ganglia has received much attention over the last two decades, as it has been implicated in many neurological and psychiatric disorders. Most of this research - in both animals and humans - attempt to understand the neural and biochemical substrates of basic motor and learning processes, and how these are affected in human patients as well as animal models of brain disorders. The current volume contains research articles and reviews describing basic, pre-clinical and clinical neuroscience research of the basal ganglia written by attendees of the 11th Triennial Meeting of the International Basal Ganglia Society (IBAGS) that was held March 3-7th, 2013 at the Princess Hotel, Eilat, Israel and by researchers of the basal ganglia. Specifically, articles in this volume include research reports on the biochemistry, computational theory, anatomy and physiology of single neurons and functional circuitry of the basal ganglia networks as well as the latest data on animal models of basal ganglia dysfunction and clinical studies in human patients.